The Development of Android-Based Learning Media (Chemdroid) on The Topic Thermochemistry to Improve The Students’ Achievement - Febrian Solikhin; Andang Wijanarko (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2021)
The application of technology in learning is currently increasingly sophisticated. The development of learning media is widely applied to make learning more flexible. in this article will discuss the development (R&D) of Chemistry on Android (Chemdroid). This study aims to determine the media's quality based on the chemistry teacher's assessment, determine the readability of the media based on the assessment of students who have received this material, and determine the impact of this media trial in chemistry learning. The development design used is ADDIE (Analysis, Design, Development, Implementation, and Evaluation). At the implementation stage, the posttest control group design was used by involving two classes as the control and experimental class. The variable measure is students achievement. The results obtained are that the Chemdroid learning media has been developed and declared valid by four experts. The assessment results by five high school chemistry teachers were Very Good, with a mean value of 3.31. The results of this assessment state that the Chemdroid learning media is suitable for use as a learning media for thermochemistry. In comparison, the readability test results by 16 students from 4 various senior high schools resulted in Good criteria with a mean of 3.24, which means that this media is legible and useful for students in various groups. The analysis of the implementation results states that the two classes have a significant difference.